An eco-friendly self-compacting concrete with recycled coarse aggregates - Oliveira, Luiz Antonio Pereira de (2013)
The potential uses of coarse recycled aggregates in the composition of SCC increases the ecological value and partly solve the issues of waste disposal sites generated by construction and demolition of structures. Thus, this paper present an experimental study of SCC properties where the normal coarse aggregates were replaced by different percentages of recycled aggregates, i.e., 0% (SCC), 10% (SCCR10), 20% (SCCR20), 30% (SCCR30) and 40% (SCCR40). The results from fresh concrete (rheological properties and self-compactability) as the hardened concrete properties (compressive strength, density and dynamic modulus of elasticity), show only minor discrepancies. From the standpoint of mechanical behaviour, the results confirm the viability to incorporate coarse recycled aggregates in the SCC demonstrating the conservative character of the currently recommended limits.